2020
DOI: 10.1055/s-0040-1702151
|View full text |Cite
|
Sign up to set email alerts
|

Unique Complications of Venous Anastomotic Couplers: A Systematic Review of the Literature

Abstract: Background Anastomotic couplers expedite venous microvascular anastomoses and have been established as an equivalent alternative to hand-sewn anastomoses. However, complications unique to the coupler such as palpability and extrusion can occur. The purpose of this study was to perform a systematic review of the literature to assess complications distinct to the venous anastomotic coupler. Methods A Medline, PubMed, EBSCO host search of articles involving anastomotic venous couplers was performed. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…While there are recognized preoperative patient-related factors that can affect flap outcomes, tissue oximetry monitoring can decrease free flap loss and improve salvage rate in the postoperative setting. 4,[11][12][13] A survey found that microsurgeons were more likely to immediately return to the operating room for a concerning tissue oximetry reading than an abnormal Doppler signal. 3 Other investigators have shown benefits of incorporating tissue oximetry in flap monitoring protocols as well.…”
Section: Discussionmentioning
confidence: 99%
“…While there are recognized preoperative patient-related factors that can affect flap outcomes, tissue oximetry monitoring can decrease free flap loss and improve salvage rate in the postoperative setting. 4,[11][12][13] A survey found that microsurgeons were more likely to immediately return to the operating room for a concerning tissue oximetry reading than an abnormal Doppler signal. 3 Other investigators have shown benefits of incorporating tissue oximetry in flap monitoring protocols as well.…”
Section: Discussionmentioning
confidence: 99%
“…Unique complications associated with these couplers have been systematically reviewed; however, the focus was only on the postoperative setting. 29 Additionally, in a direct comparison of ID couplers and venous anastomotic couplers, the only intraoperative complication discussed was vessel thrombosis and there was not a significant difference in the rate of this complication. 30 Reports of coupler ring detachment, the second most commonly reported device malfunction, had four associated adverse events.…”
Section: Discussionmentioning
confidence: 96%
“…Stanix et al 22 reported that the rates of complications and flap failure were similar between reconstructions performed using a venous coupler and those performed using hand-sewn venous anastomosis in lower extremity reconstructions, which have the highest reported rates of complications and flap failure among all anatomical regions. Conversely, in a systematic review of venous anastomotic couplers by Wu et al, 23 unique complications, such as coupler extrusion and palpability, were reported in cases with previous radiation exposure or thin, soft tissues (eg, head and neck, hands, and feet). Methods such as the use of metal stents completely buried in the target blood vessels may prevent such complications.…”
Section: Discussionmentioning
confidence: 99%